Electron and vibration structure of fluorine-containing polyamide film under high energetic electron irradiation - Pavlenko, O.L.; Sendiuk, V.A.; Dmytrenko, O.P.; Kulish, M.P.; Sheludko, E.V.; Kachkovsky, O.D.; Ilchenko, О.О.; Shlapatska, V.V. (Вопросы атомной науки и техники, 2017)
Influence of high energetic electron irradiation (Еᵢ = 1.8 МеV) on the electron and vibrational properties of fluorine containing polyamide films was studied. Nature of electron transitions and vibration bands in Raman and IR-absorption spectra in the initial state of the film was determined by quantum-chemical calculations. Results of optical absorption, Raman scattering and IR-absorption showed that irradiation of the film with dose of 1 MGy does not lead to significant changes of electron and vibrational structure. Increase of the dose to 3 MGy influences the intensity of vibration bands in Raman and IR-absorption spectra. Films that were transparent in the initial state became yellow-colored and fragile after the irradiation. Приведено дослідження впливу опромінення плівок фторвмісного поліаміду високоенергетичними електронами (Еᵢ = 1,8 МеВ) на його електронну та коливну структуру. За допомогою квантово-хімічних розрахунків встановлено природу електронних переходів та смуг КРС, а також ІЧ-поглинання у вихідному стані. Результати оптичного та ІЧ-поглинаннь, раманівського розсіяння світла показують, що дані плівки при дозі 1 МГр зберігають свою електронну та коливну структуру. Збільшення дози до 3 МГр призводить до зміни інтенсивностей коливних мод у спектрах раманівського розсіяння та ІЧ-поглинання. При даній дозі плівки втрачають прозорість, набуваючи жовтого кольору, і стають крихкими. Приведены исследования влияния облучения пленок фторсодержащего полиамида высокоэнергетическими электронами (Еᵢ = 1,8 МэВ) на его электронную и колебательную структуру. С помощью квантово-химических расчетов установлена природа электронных переходов и полос КРС, а также ИК-поглощения в исходном состоянии. Результаты оптического и ИК-поглощения, рамановского рассеяния света показывают, что данные пленки при дозе 1 МГр сохраняют свою электронную и колебательную структуру. Увеличение дозы до 3 МГр приводит к изменению интенсивностей колеблющихся мод в спектрах рамановского рассеяния и ИК-поглощения. При данной дозе пленки теряют прозрачность, приобретая желтый цвет, и становятся хрупкими.